Depth Theology and Depth Islam: Abraham Joshua Heschel and Nurcholish Madjid on Religious Pluralism - Media Zainul Bahri (Al-Albab, 2019)
The work attempts to elucidate the idea of religious pluralism of two very important figures in the traditions of Judaism and Islam: Abraham Joshua Heschel (1907-1972) and Nurcholish Madjid (1939-2005). Both figures are interesting to compare for some very important reasons. Although somewhat different, there is much in common between the two, especially in terms of their arguments on the issue of religious pluralism. Their ideas of religious pluralism are based on what the so- called “Depth Theology” (DT) and “Depth Islam” (DI). DT and DI are different from the usual theological dogmas that contain concepts and structures. DT and DI are not literal and superficial forms of religion. Their religious understanding went beyond the literal texts to look for the principles and spirit of religion in appreciating humanity, diversity and peace.  In the context of inter-religious tensions due to suspicion, hatred, and hostility, the depth-theology of Heschel and the depth Islam of Madjid find their significance.